Tax planning of R&D intensive multinationals - Jost H. Heckemeyer; Katharina Richter; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The allocation of management and control in the business decision process finds expression in the coordination intensity between agents in the firm. We develop and test a theory, based on the organizational design literature, for the intensity in which the tax department strives to coordinate with managers from other business units in order to intervene in investment decisions. Our theoretical considerations predict that R&D intensity is an important determinant of the tax department's role. Using data from a confidential survey taken in 2012 of top financial and tax managers of very large multinational companies, representing 8% of business R&D spending in the OECD, we indeed find supporting evidence that in R&D intensive multinational firms the tax department operates more as a controller than as a manager. In particular, tax departments of R&D intensive firms make less tax planning effort, are less ambitious to minimize the tax burden of the firm, are later involved in the decision-making process of a new investment project, but are more likely to have a veto right in the decision on a new investment project as compared to less R&D intensive firms. Conditional on R&D intensity, however, the level of intangible assets in the firm is associated with more tax planning efforts and ambitions. Our results are statistically significant and robust towards several sensitivity checks.
urn:nbn:de:bsz:180-madoc-374624
Keywords: H25; L22; M41; 330; corporate taxation; organizational design; survey data